HYGIENIC CARE OF CHILDREN'S SKIN - R. Adam ("Paediatrician" Publishers LLC, 2010)
Children's skin under nappy needs special defense from irritative action of urine and faeces and, therefore, prophylaxis of nappy dermatitis is necessary. It means that disposable nappy absorbing faeces and urine and special staff for skin cleaning should be used. There are several factors conductive to dermatitis: prolonged irritation with excrements, change of skin pH or increase of its hydratation and disorders of skin micro flora. During last decades there is a significant progress in understanding of these factors, and it resulted in production of more and more perfect stuff for defense of children's skin. Improved design of nappies and development of pH-buffer wipes for babies increased the quality of skin care. Key words: children, skin, hygienic care. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(5):90-94)